Determination of Shear Strength of Organic Soil in Kashmir (International Journal of Innovative Research in Engineering & Management, 2022)
As a conference and tourist resort hub,  Kashmir is one of India’s most rapidly expanding states.  There is a lot of building work going on right now. It's also  projected that there will be a lot more building in the future.  However, there has been relatively little research on the  engineering qualities of Kashmir valley’s soils. Shear  strength, or the capacity to resist sliding along internal  surfaces inside a soil mass, is one of the most essential  engineering qualities of soil. All stability assessments in  geotechnical engineering, whether they be for foundations,  slopes of cuttings, or earth dams, require a fundamental  understanding of this soil engineering feature. The shear  strength parameters of Kashmir’s alluvial soil are going to be  investigated in this study. The shear strength parameters (c  and Ф) are investigated using disturbed soil samples that  have been remoulded with various densities and water  contents to imitate field conditions. Infrastructural  developments have now progressed in Jammu and Kashmir  and strength evaluation of peat remains complex and  uncertain. Considering failures of infrastructures resulting  from inappropriate measurement of peat shear strength, this  research paper present on the shear strength of peat and the  modification of existing testing methods to assess its strength  in the laboratory and on the field. The initial part of this research is the laboratory testing of peat specimens.  Scanning electron microscopy (SEM), triaxial tests are  conducted to characterise the morphology, compressibility  and shear strength properties of peat. The results of the  microstructural and compressibility analysis are presented  together with the triaxial stress-strain analysis. The analysed  results show the effect of decomposition on peat and shear  strength characteristics.
Keywords: Shear Strength; Peat; Organic Soil; Jammu and Kashmir; SEM